AB1180 THE EVOLUTION OF AN FLS IN SEARCH OF EXCELLENCE: THE EXPERIENCE OF GRAN CANARIA. (13th June 2020) - Naranjo, A.; Molina, A.; Sepúlveda, C.; Torres, C.; Santana, F.; Rubiño, F.; López, R.; Ojeda, S.
Abstract : Background: The implementation of an FLS in the Spanish public health system is not an easy task since there are no official plans for the incorporation of personnel dedicated to the unit Objectives: To expose the consolidation and improvement of an FLS after its implementation as well as the problems that have arisen over time. Methods: The health program for secondary fracture prevention was implemented in 2012. Initially worked with the same staff assigned to the Rheumatology service, since 2016 we have a part-time support nurse. Patients are identified from the emergency registry and, more recently, from patients admitted for hip fracture and treated in a monographic osteoporosis clinic. The baseline visit consists of consultation with the nurse, DXA and bone metabolism analytics. Falling patients are referred to a fall prevention school. Most patients are referred to their primary care physician to start a treatment. Results: Of the 2, 416 patients attended the baseline visit, 30% were forearm fractures, 27% hip, 20% humerus, 10% spine and 11% other fractures. In comparison to 2012, in 2019 the monthly average of patients has doubled, increased the number of hip and spine fractures, and increased the percentage of captured patients (Table). In spite of consolidating the unit, getting a support nurse for the admitted patients and establishing a solid alliance with primary care, it is pending the involvement of Primary Care Nurses and start first prescription at the hospital. Conclusion: We present the achievements made by our FLS along 8 years and the difficulties within the Spanish public health system. Disclosure of Interests: Antonio Naranjo Grant/research support from: amgen, Consultant of: UCB, Speakers bureau: AMGEN, Amparo Molina Speakers bureau: AMGEN, STADA, Cristina Sepúlveda: None declared, Candelaria Torres: None declared, Fabiola Santana: None declared, Francisco Rubiño: None declared, Rubén López: None declared, Soledad Ojeda Speakers bureau: AMGEN, LILLY, GEBRO